POLYMORPHISM OF CYTOCHROME P450 2A6 (CYP2A6*1 AND CYP2A6*4) AMONG JAVANESE INDONESIAN SMOKER AND NON SMOKER - Christine Patramurti; Sugiyanto .; Arief Nurrochmad; Sudibyo Martono (Indonesian Journal of Pharmacy, 2015)
Cytochrome P450 2A6 (CYP2A6) is the principal enzyme involved in the metabolic activation of tobacco-specific nitrosamines to their ultimate carcinogenic forms and metabolism of nicotine. The present study was developed to investigate the genetic polymorphism of CYP2A6 in Javanese Indonesian subjects carrying the CYP2A6*1 allele and the CYP2A6*4. The whole gene deletion of CYP2A6 (CYP2A6*4) may inhibit smokers from giving up smoking, but appears to function as a protective factor against to some cancer. However, the investigation of these allele, a major functional polymorphisms common in Asian populations, have not been reported among Javanese Indonesian population. A single polymerase chain reaction-restriction fragment length polymorphism was used to resolve the genotypes into CYP2A6*1 (wild type) and CYP2A6*4 (CYP2A6del). The sample studied consisted of 100 healthy subject that consist of 50 non smokers and 50 smoker from Javanese Indonesian population. The allele frequencies of *1 (wild type) and *4, were 47.5 and 52.5%, respectively. When the two allel were considered simultaneously, among the non-smokers, 45% were genotyped for CYP2A6*1/*4 and 5% were genotyped for CYP2A6*4/*4; on the other hand all of the smoker were genotyped for CYP2A6*1/*4 and there was no homozygote of wild type. Based on the data collected, it could be concluded that the polymorphism of CYP2A6 were detected in among Javanese population sample study and the allele frequencies of CYP2A6*4 were high.Key word: Polymorphism, CYP2A6*1, CYP2A6*4, Javanese Indonesian